Antifungal Pharmacology: Current Concepts (International Journal of Food and Nutritional Sciences, 2022)
Drug toxicity is no longer the primary limiting factor in the management of invasive mycoses thanks to the development of new antifungal drugs during the past ten years, such as echinocandins and second-generation triazoles. However, a lot of these more recent antifungal medications have significant restrictions on their range of activity, pharmacokinetics, and special propensity for pharmacokinetic drug-drug interactions and peculiar toxicities brought on by prolonged usage. In order to increase the safety and effectiveness of systemic antifungal therapy, this article discusses essential pharmacological characteristics of systemic antifungal drugs as well as developing methodologies, such as pharmacokinetic-pharmacodynamic optimization and therapeutic drug monitoring.